THE ROLE OF CONCELORS IN CONSIDERING YOUTH REPRODUCTION PROBLEMS IN TEENAGER (PIK-R) INFORMATION AND CONSELING CENTER OF BATUJAJAR KECAMATAN BANDUNG BARAT REGENCY - I Made Erie Sucipta Eka Surya; Abu Huraerah (SAMPURASUN, 2018)
This research is titled: " The Role of Peer of Teenager's Reproductive Health Problem Counselor in Overcoming at PIK-R Batujajar Sub District Formation, Bandung Barat Regency". PIK-R is an information center and counseling for teenagers under supervised by BKKBN (Familiy Planning Board of Republic of Indonesia). The aims and objectives of this research were: To describe the role of peer counselor in overcoming teenager's reproductive health problem. To identify various factors that influence the role of peer counselor in overcoming teenager's reproductive health To identify several efforts to overcome barrier on peer counselor in overcoming teenager's reproductive health. Practical implications of social work intervention on peer counselor in overcoming teenager's reproductive health. The research method employed a qualitative approached relied largely on the interpretative and critical approaches to social work science. The data gathering is used a documenting real events, recording what information (with words, gestures, and tones), observing specific behaviors, written documents, and participant observation. In this research, the number of informants were 7 teenagers related to reproductive health counseling . Research finding the role of teenagers in counseling on reproductive health is still weak due to systems that could not easily be accessed by them . The group dynamic is very important component in reproductive health counseling because the discourse within the group will cover eproductive health, and addresses the reproductive processes, fuctions and systems at all stages of life, however this condition also remains weak. Recommendations went to BKKBN in order to create a synergy program for synergy health between PIK-R, Official Staff of reproductive health at Batujajar Sub District and DP2KBP3A to build data integrity based on digital online related to overcome reproductive health of teenagers.